FACTORS AFFECTING INDIVIDUAL TAXPAYER COMPLIANCE AT TABANAN TAX OFFICE - Anik Yuesti; Ni Putu Candra Santi Lestari; I Gusti Agung Arista Pradnyani; Yura Karlinda Wiasa Putri (Jurnal Akuntansi dan Bisnis, 2025)
This study examines the factors influencing individual taxpayer compliance (WPOP) at the Tabanan Tax Office (KPP Pratama Tabanan), focusing on tax socialization, tax knowledge, tax sanctions, taxpayer awareness, and tax rates. Using a quantitative approach with data from 100 respondents, the results reveal that tax socialization, tax knowledge, sanctions, and taxpayer awareness positively affect compliance, while tax rates have a positive impact, though weaker. These findings suggest that improving tax awareness and knowledge, alongside stricter enforcement of sanctions, is crucial for enhancing compliance. The study also recommends further research with broader variables and geographic coverage to deepen understanding and contribute to more effective policy reforms.